Music Therapy with Patients with Personality Disorder: Advantages and Challenges - Hannibal, Niels; Strehlow, Gitta (Voices: A World Forum for Music Therapy, 2024)
This clinically oriented article reflects on music therapy with patients with a personality disorder diagnosis, focusing on music improvisation and the advantages and challenges it may provide for both patient and therapist. The method used is reflexive and based on a combination of many years of clinical experience and theoretical reflection. The article has four parts. The first part describes our approach to music therapy. The second part presents our view on challenges in music therapy with patients with a personality disorder (PD) and specifically borderline personality disorder (BPD) issues. The third part presents our view on the advantages of music therapy with this client group and the fourth part is a discussion. The discussion has three topics: 1. Does this article present a more nuanced picture of music therapy with a more diverse understanding of challenges and advantages? 2. What is the relationship between challenges/advantages and rupture/repair? 3. How does music therapy relate to common factor theory?